Factors affecting online shopping behaviour in Malaysia / Mohamad Shamsul Aizat Mohd Salleh - Mohd Salleh, Mohamad Shamsul Aizat (2013)
Purpose - The purpose of this study is to identify the key factors influencing Malaysian’s online shopping behaviour. Specifically to determine whether website design, reliability, customer service, and trust influence Malaysian’s online shopping behaviour. In addition, to determine which factors has the most impact towards online shopping behaviour. Design/Methodology/Approach - For the completion of this study, the researcher used stratified sampling technique, where the questionnaires were distributed to 64 Malay, 28 Chinese and 8 Indian respondents all around Kuala Lumpur. The research design used in this study is descriptive research design. Findings – The findings of this study indicate that website design, reliability, customer service, and trust have influences on online shopping behaviour in Malaysia. Based on the findings, website design has the most impact towards online shopping behaviour, followed by customer service, trust, and reliability. Significance of study - Based on this study, online retailers can gain more understanding in conducting online business in Malaysia. This study will be use for reference and as additional information for students in marketing or other business program. Originality/ Value - The paper draws attention to a rather neglected issue of key factors that influence online shopping behaviour in Malaysia.